Characteristics of the system of evaluation of learning in the training of students of the UNHEVAL - Monago Malpartida, Jani (2009)
The purpose of the research was to determine the degree of influence of the characteristics of the system of assessment of learning in the Vocational Student of the UNHEVAL. The type of research was the descriptive-explanatory design transectional, causal-correlational and retrospective, we applied a non-probability sampling with a convenience sample of 34% of the population authority. Was applied to opinion polls: 01 = planning = 02 = 03 enforcement and implementation of the evaluation. Also the analysis of the records of letters. The results reveal a low correlation between the characteristics of the evaluation system of learning and vocational training, which demonstrates that there is a direct and significant influence at low level features of the evaluation system of learning, low training of students.